Inhibition of HDAC6 activity protects dopaminergic neurons from alpha-synuclein toxicity - Francelle, Laetitia; Outeiro, Tiago F.; Rappold, Gudrun (Scientific reports, 2020)
The neuropathological hallmarks of Parkinson’s disease include preferential vulnerability of dopaminergic neurons of the substantia nigra pars compacta, and accumulation of intraneuronal protein inclusions known as Lewy bodies. These inclusions contain, among other proteins, aggregated alpha-synuclein and histone deacetylase 6 (HDAC6). In our study we found that selective inhibition of HDAC6 activity by Tubastatin A has protective effects in a rat model of Parkinson’s disease. We provide evidence that this protection may be due to the activation of chaperone-mediated autophagy through the up-regulation of key members of this pathway. Moreover, Tubastatin A significantly inhibited the expression of a toxic form of alpha-synuclein that is phosphorylated at serine position 129. Tubastatin A treatment also permitted to partially modulate neuroinflammation. Taken together, our study highlights the neuroprotective effects of Tubastatin A in a rat model of Parkinson’s disease and provides mechanistic insight in Tubastatin A-mediated protection against alpha-synuclein toxicity and substantia nigra degeneration. These findings are of potential therapeutic value in Parkinson’s disease and other synucleinopathies.
Gesehen am 23.09.2020